2021
DOI: 10.1108/ijmpb-05-2020-0159
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ethical leadership on project success: the mediating role of trust and knowledge sharing

Abstract: PurposeAlthough the use of project teams is on the rise, there is a limited understanding of how project managers can ensure project team success. Research to date is relatively broad and does not pinpoint how and why leadership influences success in a project team context. Along these lines, we draw from social learning theory to illustrate that ethical leadership influences project success through leader trust and knowledge sharing.Design/methodology/approachWe collected data from 175 project team members fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 79 publications
2
74
0
Order By: Relevance
“…In addition, many studies have been conducted on various types of leadership linked to organizational effectiveness levels such as job satisfaction, organizational immersion, and organizational citizenship behaviors of organization members [40,77,78]. In particular, according to the contingency approach, the effectiveness of leadership in making high collective achievements depends on the styles (e.g., servant, ethical, authentic leadership) by which leaders control the situation of organization members and positively influence various factors (e.g., human respect, potential, ethics) [82][83][84]. All things considered, the contingency approach of leadership was utilized and applied as a foundational theory in the path of sustainable leadership → organizational citizenship behavior in this study.…”
Section: Contingency Approach Of Leadershipmentioning
confidence: 99%
“…In addition, many studies have been conducted on various types of leadership linked to organizational effectiveness levels such as job satisfaction, organizational immersion, and organizational citizenship behaviors of organization members [40,77,78]. In particular, according to the contingency approach, the effectiveness of leadership in making high collective achievements depends on the styles (e.g., servant, ethical, authentic leadership) by which leaders control the situation of organization members and positively influence various factors (e.g., human respect, potential, ethics) [82][83][84]. All things considered, the contingency approach of leadership was utilized and applied as a foundational theory in the path of sustainable leadership → organizational citizenship behavior in this study.…”
Section: Contingency Approach Of Leadershipmentioning
confidence: 99%
“…EL effects on employee’s knowledge sharing behavior was studied from a social perspective ( Ganguly et al, 2019 ), personal characteristics ( Kim and Shim, 2018 ), and cultural influences ( Liu et al, 2018 ). Ethical leadership has significant relationship with knowledge sharing ( Bhatti et al, 2021 ). Most studies have demonstrated that leadership significantly motivates individuals to share their knowledge with colleagues, regardless of the organizational setting ( Ali et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the ethical nature of knowledge sharing and the significance of organization leadership styles, more and more recent studies have demonstrated that ethical leadership is the most appropriate leadership approach to encourage employees to engage in knowledge sharing (Bavik, et al, 2017; Bhatti et al, 2020; Bhatti et al, 2021; Lu et al, 2019). It has been found in many previous studies that ethical leadership negatively associated with knowledge hiding and a lot of valuable management practices have been explored to discourage employees to hide knowledge (Abdullah et al, 2019; Men et al, 2020; Tang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%